The dual crisis in Irish foreign policy: the economic crash and Brexit in a volatile European landscape. Issue 4 (2nd October 2019) - Rees, Nicholas; O'Brennan, John
ABSTRACT: This article considers the impact of the 2008–10 financial crisis and the UK's 2016 Brexit decision as a 'dual crisis' which impacted significantly on Irish foreign policy over the past decade. It argues that though Ireland's foreign policy has remained remarkably consistent over time, the 'dual crisis' placed considerable pressure on state capacity and institutional resources. Ireland's financial implosion carried with it potentially catastrophic consequences for the Eurozone and thus successive governments placed a particular priority on restoring Ireland's tarnished reputation within the European Union. At the same time, Irish foreign policy was 'rebooted' to take on a more muscular promotion of Irish economic interests across the globe. Brexit constituted an existential threat to the island of Ireland, and, in particular the peace process marked by the 1998 Good Friday Agreement. The Brexit crisis set in train a determined effort by Irish policy-makers to both confirm the EU as Ireland's 'geopolitical centre of gravity' and re-position the country within the Union, as the need for new allies and coalition partners became evident following the United Kingdom's planned departure.